Institutions, production, and marketing of maize in Zimbabwe: case of Marondera district of Mashonaland East province, a two-stage model - Mafuse, Never; Mushunje, Abbysinia; Zivenge, Emmanuel (Food & Agribusiness Management (FABM), 2021)
This study evaluated the influence of institutions on production and marketing efficiency of A1 maize resettled farmers in Marondera district. Data Envelopment Analysis was used to determine the efficiency scores of farmers while Tobit model was used to determine institutional factors influencing technical efficiency for both production and marketing. A multistage sampling procedure was used to select 343 farmers from Marondera District. Results showed that, farmers are technically, allocatively and economically inefficient for both production and marketing stages. Farmers are performing better at production stage than at marketing technically while there is better allocative and economic efficiency at marketing stage. Formal maize markets are more efficient than informal markets. Results for determinants of technical efficiency at production stage showed that, cattle ownership, farming experience, access to credit and social capital significantly influence maize production efficiency while access to credit, access to market, distance to market and road condition influences marketing efficiency. It can be therefore, recommended to the government of Zimbabwe to improve the institutional environment and arrangement in terms of provision of better roads, access to credit, access to markets so as to improve both production and marketing efficiency. Farmers are also recommended to join or form famer organisations as this will assist in improving both production and marketing efficiency.
Keywords: Maize production; Maize marketing